Temporal Control of Gelation and Polymerization Fronts Driven by an Autocatalytic Enzyme Reaction. Issue 6 (6th January 2016) - Jee, Elizabeth; Bánsági, Tamás; Taylor, Annette F.; Pojman, John A.
Abstract: Chemical systems that remain kinetically dormant until activated have numerous applications in materials science. Herein we present a method for the control of gelation that exploits an inbuilt switch: the increase in pH after an induction period in the urease‐catalyzed hydrolysis of urea was used to trigger the base‐catalyzed Michael addition of a water‐soluble trithiol to a polyethylene glycol diacrylate. The time to gelation (minutes to hours) was either preset through the initial concentrations or the reaction was initiated locally by a base, thus resulting in polymerization fronts that converted the mixture from a liquid into a gel (ca. 0.1 mm min −1 ). The rate of hydrolytic degradation of the hydrogel depended on the initial concentrations, thus resulting in a gel lifetime of hours to months. In this way, temporal programming of gelation was possible under mild conditions by using the output of an autocatalytic enzyme reaction to drive both the polymerization and subsequent degradation of a hydrogel. Abstract : In control at the front line : By coupling a base‐catalyzed thiol‐Michael addition with a base‐producing autocatalytic enzyme reaction, it was possible to program gelation and generate propagating polymerization fronts (see picture; ETTMP is a polymeric trithiol, PEGDA is poly(ethylene glycol) diacrylate). The rate of hydrolytic degradation of the resulting hydrogel depended on the initial concentrations of the components of the system.